CONFIRMATORY FACTOR ANALYSIS (CFA) OF THE ACCOUNTING TEACHER PROFESSIONAL IDENTITY SCALE (ATPIS) - Muhammad Fahmi Johan Syah; Sharul Effendy Janudin; Mahaliza Mansor (Jurnal Pendidikan Ilmu Sosial, 2022)
This study aims to test the ATPIS which has previously been developed using exploratory Factor Analysis (EFA). This scale consists of five latent factors with 23 manifest variable items. The target population is Indonesian accounting teachers in Central Java who are members of the Accounting Subject Teachers' Conference (MGMP), totaling 1747 people. From the total population, 351 respondents were selected. The data analysis technique of this research was CFA and model fit analysis. The results showed that the proposed model was proven to be valid where the ATPI loading factor for the five factors had a value of more than 0.70. In contrast, the latent sub-construct variable in the manifest variable had a loading factor of more than 0.50. Revision of the model was done by eliminating one latent variable, APC3, a manifest variable from active in professional communities. The results of the model revision indicated that the overall loading factor value increased with the better model fit. Therefore, this ATPIS can be utilized as an instrument to measure the professional identity of accounting teachers. Nevertheless, it is still possible to develop a revised version of ATPIS with several new sub-construct latent variables that have not been tested.